Can Rainfall Explain the Variability of Sugarbeet Root and Sugar Yield Across North Dakota and Minnesota?. Issue 6 (4th November 2020) - Chatterjee, Amitava
Abstract : Sugarbeet production regions of North Dakota and Minnesota contribute more than half of the production nationally. Across this region, sugarbeet yield and sugar content vary widely from north to south. The study described in this article used statistical analyses of five years (2013–2017) of county‐wise monthly rainfall data to interpret the spatial variation of sugarbeet yield and quality. Earn 0.5 CEUs in Crop Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/857 .